2021
DOI: 10.1145/3448737
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Link Quality Fluctuation in Mobile Wireless Sensor Networks

Abstract: Wireless sensor networks accommodating the mobility of nodes will play important roles in the future. In residential, rehabilitation, and clinical settings, sensor nodes can be attached to the body of a patient for long-term and uninterrupted monitoring of vital biomedical signals. Likewise, in industrial settings, workers as well as mobile robots can carry sensor nodes to augment their perception and to seamlessly interact with their environments. Nevertheless, such applications require reliable communication… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 39 publications
0
5
0
Order By: Relevance
“…Due to its resilience to wireless interference and multi-path fading, multichannel communication can effectively improve the reliability of LLN under cross-technology interference, which has received extensive attention from academia and industry. However, existing LQE metrics and models are generally established and verified under the single-channel scenario [ 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 ], and most of them are under the interference-free channel [ 10 , 11 , 12 , 13 , 14 , 15 , 16 , 18 , 19 ]. In the multichannel scenario, as the channels used will change from time to time, whether these metrics and models are still applicable is hard to judge directly because of the lack of corresponding studies.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Due to its resilience to wireless interference and multi-path fading, multichannel communication can effectively improve the reliability of LLN under cross-technology interference, which has received extensive attention from academia and industry. However, existing LQE metrics and models are generally established and verified under the single-channel scenario [ 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 ], and most of them are under the interference-free channel [ 10 , 11 , 12 , 13 , 14 , 15 , 16 , 18 , 19 ]. In the multichannel scenario, as the channels used will change from time to time, whether these metrics and models are still applicable is hard to judge directly because of the lack of corresponding studies.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, node mobility or cross-technology interference (CTI) will also affect the accuracy of LQE. Wen et al [ 19 ] showed that low-power links are highly sensitive to node mobility and predicting the existence and range of transitional regions is more difficult. Barać et al [ 20 ] showed that LQI and RSSI obtained from interfered WSN links are deceptive and cannot be used to assess link quality accurately.…”
Section: Related Workmentioning
confidence: 99%
See 2 more Smart Citations
“…In order to analyze the performance of the networks, we studied the data workflow, the battery consumption, the rate of data loss during data transmission and the received signal strength over a given period. These metrics are those classically used in the literature to qualify wireless sensor networks [ 45 , 46 ].…”
Section: Methodsmentioning
confidence: 99%